An Experimental Characterization on the Acoustic Performance of Forward/Rearward Retraction of a Nose Landing Gear - Bennett, Gareth; Liang, Yong; Zhao, Kun; Chen, Yingchun; Zhang, Longjun (My University, 2019)
The modern undercarriage system of a large aircraft normally requires the landing gear to be retractable. The nose landing gear, installed in the front of the fuselage, is retracted either forward or rearward. In the forward/rearward retraction system, the landing gear is normally installed to the trailing/leading side of the bay. When the incoming flow passes the landing gear as well as the bay, the installation that corresponds to the forward/rearward retraction system has a significant impact on the coupling flow and the associated noise of the landing gear and the bay. In this paper, acoustic performance of the forward/rearward retraction of the nose landing gear was discussed based on experiment. The landing gear bay was simplified as a rectangular cavity, and tests were conducted in an aeroacoustics wind tunnel. The cavity oscillation was first analyzed with different incoming speeds. Then, the landing gear model was installed close to the trailing and the leading side of the cavity, respectively. It was observed that installation close to the leading side can help disturb the shear layer so as to suppress the oscillation, while the trailing one can make the landing gear itself produce lower noise. Accordingly, conclusions on the acoustic performance of the forward/rearward retraction of the nose landing gear are made.
Keywords: Aircraft; Acoustic performance; Nose landing gear